2008
DOI: 10.1038/mp.2008.40
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drug mechanisms: links between therapeutic effects, metabolic side effects and the insulin signaling pathway

Abstract: The exact therapeutic mechanism of action of antipsychotic drugs remains unclear. Recent evidence has shown that second-generation antipsychotic drugs (SGAs) are differentially associated with metabolic side effects compared to first-generation antipsychotic drugs (FGAs). Their proclivity to cause metabolic disturbances correlates, to some degree, with their comparative efficacy. This is particularly the case for clozapine and olanzapine. In addition, the insulin signaling pathway is vital for normal brain dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 113 publications
1
45
0
Order By: Relevance
“…20,21 Insulin receptors are expressed in many brain areas, and abnormalities in brain insulin signalling have been reported in patients with schizophrenia, with evidence suggesting that antipsychotics may also disrupt these pathways. 22 Linking these disruptions to metabolic dysfunction, it is now well established that insulin, separate from its effects on liver receptors, regulates hepatic glucose production in rodents via hypothalamic insulin receptors. 23,24 Moreover, intranasal insulin administration to healthy humans decreases endogenous glucose production.…”
mentioning
confidence: 99%
“…20,21 Insulin receptors are expressed in many brain areas, and abnormalities in brain insulin signalling have been reported in patients with schizophrenia, with evidence suggesting that antipsychotics may also disrupt these pathways. 22 Linking these disruptions to metabolic dysfunction, it is now well established that insulin, separate from its effects on liver receptors, regulates hepatic glucose production in rodents via hypothalamic insulin receptors. 23,24 Moreover, intranasal insulin administration to healthy humans decreases endogenous glucose production.…”
mentioning
confidence: 99%
“…In addition, this interaction may constitute a molecular mechanism involved in many, if not all, side effects of clozapine. Considering the high propensity of clozapine to induce these side effects, correlated with its high antipsychotic properties compared with other atypical neuroleptics, (Leucht et al 2009;Tandon et al 2008), it was recently hypothesized that the therapeutic antipsychotic and adverse effects of antipsychotic drugs might be related to a common pharmacologic mechanism (Girgis et al 2008). The interaction with brain histamine receptors might be a part of this common mechanism.…”
Section: Resultsmentioning
confidence: 98%
“…In two recent studies, central administration of IGF1 in mice has shown to have an antidepressant-like effect [Hoshaw et al, 2005;Malberg et al, 2007]. A recent review has linked antipsychotic drug mechanisms and the insulin-signaling pathway which may be abnormal in schizophrenia [Girgis et al, 2008].…”
Section: Introductionmentioning
confidence: 98%